Research Paper : Consolidating the yield gain by exploiting genotype × management interaction in wheat - Sagar, Vidya; Yadav, Rajbir; Jain, Neelu; Gaikwad, K.B.; Prabhu, K.V. (The Indian Journal of Genetics and Plant Breeding, 2017)
An experiment was conducted with 42 differentially adapted genotypes of wheat for two subsequent years (2011-13) to quantify the genotype × management interaction using additive main effect and multiplicative interaction (AMMI) and genotype main effect (G) plus genotype by environment interaction (GGE) methods. The material was evaluated in three different environments namely, permanent bed (zero tillage) with full residue retention (CA), freshly prepared raised bed with no residue (CTRB) and conventionally tilled and seeded condition i.e. flat bed (CTFB). Genotypic differences for the traits having relevance in adaptation were found significant. Environment followed by genotype × management interaction were found to be the major source of variation for yield, biomass, harvest index (HI) and number of tillers. AMMI biplot pooled six environments (3 management systems and 2 years) into three groups and grouping was slightly different from the grouping done by GGE. As per AMMI analysis, discriminating ability of CA even during stressed year was equal to that of CTFB during more productive year. GGE identified permanent raised bed with residue as most representative and discriminating environment. GGE identified HD3115, HD3117, CSW2, CSW16, CSW18, CSW23 and CSW25 with specific adaptation for CA and CSW35, CTRB1813, CTRB1816, CTRB1817 and CTFB4566 for CTRB. The results clearly suggest that selection and evaluations of breeding material under CA lead to identification of genotypes broadly adapted to other management practices but no vice-versa. CA is the most representative and informative environment and identification and release of CA specific variety can further consolidate the yield.